Bowling alone or bowling at all? The effect of unemployment on social participation - Lars Kunze; Nicolai Suppa (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This article examines the impact of unemployment on social participation for Germany using the German Socio-Economic Panel. We find significant negative, robust and, for some activities, lasting effects of unemployment on social participation. Causality is established by focussing on plant closures as exogenous entries into unemployment. Social norms, labor market prospects and the perception of individual failure are shown to be relevant for explaining these findings. Furthermore, our results not only (i) provide novel insights into the determinants of the unemployed's unhappiness but also (ii) highlight an hitherto unexplored channel through which unemployment influences economic outcomes, namely by altering the long-run level of social capital, and (iii) point to an alternative explanation of unemployment hysteresis based on access to information.
Keywords: J64; I31; 330; unemployment; social participation; plant closure; fixed effects; well-being